Comparison of Large-bore Intercostal Catheter and Small-Bore Ambulatory Pleural Drain in the Management of Pleural Effusion - E., Ekpe E.; F., Uduma; V., Umoh; MC., Ikpe; C., Eyo; AF., Akpan (International Journal of Innovative Research in Medical Science, 2019)
Background: The use of conventional chest tube and underwater seal bottle (CCT) for pleural drainage (PD) makes the treatment expensive, immediately un-affordable by more than 80% of the patients in Nigeria, and also immobilizes the patients with the attendant risks. To curtail the above mentioned problems, some researchers have reported the use of one-way valve and drainage bag for PD. Objective: To evaluate and compare PD using urobag versus CCT Methodology: Prospective randomized study of adult patients with pleural effusion who had PD with CCT and urobag respectively. Results: Before PD and at 30 minutes into the drainage, no patient in the two groups had normal respiratory rate (RR), but by 30 minutes before removal of the pleural drain, 80.5% in the CCT group and 69.2% in the urobag group had achieved normal RR. And by the 30 days follow up assessment, 100% in both groups maintained normal RR (p=0.459). The equivalent figures evaluating the patients for peripheral arterial oxygen saturation showed subnormal saturation in all patients in the two groups at 30 minutes before PD, normal saturation in 22% of patients in CCT group versus zero percent in the urobag group at 30 minutes after commencement of PD (p<0.0001). At 30 minutes before removal of pleural drain saturation was normal in 97.6% of the CCT and 84.6% of the urobag group. By 30 days follow up, saturation became normal in 97.6% of CCT group versus 100% of urobag group. Lung expansion assessed with chest radiographs at 30 minutes before pleural drainage showed that no patient in the two groups had fully expanded lung. However at 30 minutes after pleural drainage 46.3% in the CCT group versus 53.8% in the urobag group had complete lung expansion. These figures rose to 97.6% and 100% respectively at 30 minutes before removal of pleural drain and at 30 days follow-up (p=0.823). Duration of drainage of pleural effusion was less than 7 days in 92.7% of patients on CCT and in 92.3% of the urobag group. Length of hospital stay analysis showed that length of stay was shorter than 10 days in 97.6% and 100% of the CCT and urobag groups respectively. Complications attributable to the drainage systems were negligible. Conclusion: Pleural drainage with urobag and CCT all result in acceptable outcome of drainage.